A tripodal benzylene-linked trisamidophosphine ligand scaffold: synthesis and coordination chemistry with group(IV) metals - Batke, Sonja; Sietzen, Malte; Wadepohl, Hubert; Ballmann, Joachim (Inorganic chemistry, 2014)
A new tripodal trisamidophosphine ligand (1) based on the trisbenzylphosphine backbone has been synthesized in three steps starting from NaPH2 and phthaloyl-protected 2-aminobenzyl bromide. At elevated temperatures, 1 reacts directly with M(NMe2)4 (M = Zr, Hf) to afford the dimethylamido complexes [PN3]M(NMe2) (M = Zr, Hf) (2), which are easily converted into the corresponding triflates [PN3]MOTf (M = Zr, Hf) (3) via reaction with triethylsilyl trifluoromethanesulfonate. The related titanium chloro complex [PN3]TiCl (4-Ti) is obtained from 1 and Bn3TiCl via protonolysis. Triple deprotonation of 1 with n-butyllithium affords the tris-lithium salt Li3[PN3] (1-Li), which serves as a common starting material for the preparation of all the group(IV) chlorides [PN3]MCl (M = Ti, Zr, Hf) (4). Upon treatment of 4-Ti with Bn2Mg(thf)2, formation of a benzyltitanium species is observed, which is converted cleanly into a ligand-CH-activated species (5-Ti).